2013
DOI: 10.1002/ppsc.201300024
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Pressure and Temperature Dual‐Responsive Polystyrene Microbeads

Abstract: A facile approach to the synthesis of pressure and temperature dual‐responsive polystyrene (PS) microbeads with controlled sizes via dispersion polymerization is described. Three different luminophors are selected and directly introduced into the reaction system and thus incorporated into the resultant PS microbeads during polymerization. By manipulating the reaction conditions, including concentrations of the initiator and monomer, polarity of the reaction medium, and injection rate for the monomer, uniform P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The range of response times at 90% rise time due to the shock wave spreads from 26 μs to 1582 μs. For reference, the response times of polystyrene microbeads (following previous procedures 25 are also included, which show that they are the largest response times, which is consistent with previous results. 1 The polystyrene and silica microbead response time comparison is also shown in Figure 4.…”
Section: B Response Time Resultssupporting
confidence: 87%
“…The range of response times at 90% rise time due to the shock wave spreads from 26 μs to 1582 μs. For reference, the response times of polystyrene microbeads (following previous procedures 25 are also included, which show that they are the largest response times, which is consistent with previous results. 1 The polystyrene and silica microbead response time comparison is also shown in Figure 4.…”
Section: B Response Time Resultssupporting
confidence: 87%
“…Furthermore, to the authors knowledge, other sensitivities of the luminescence intensity of either species to their chemical environment, such as pH value, have not been reported. Zhu et al (2013) synthesized pressure and temperature dual-responsive PS-particles using EuTTA as the temperature sensitive dye and Coumarin 6 as the reference dye. The authors found a large temperature dependency of EuTTA in the order of 2% − K −1 .…”
Section: Characterization Of Eutta/perylene Tracer Particlesmentioning
confidence: 99%
“…With increase of the reaction time, an increase in the T d (by 6,9,13,13,14, and 17 8C, shown in Table III) is also observed. The results of GPC (Table II) indicate the enhanced thermal performance is not due to the increase of molecular weight.…”
Section: Molecular Weight and Pdi Of Pmma Copolymer And Polymer Extrmentioning
confidence: 71%
“…[1][2][3] It is known that the performance of the polymer microspheres greatly lies on their morphology. 6,7 Among them, feeding ways and reaction time as significant factors have been investigated to obtain controllable morphology of polymer microspheres. 6,7 Among them, feeding ways and reaction time as significant factors have been investigated to obtain controllable morphology of polymer microspheres.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation